1995
DOI: 10.1007/bf00133177
|View full text |Cite
|
Sign up to set email alerts
|

Kohl: a hazardous eyeliner

Abstract: Kohl is a widely used traditional cosmetic. It is mainly worn around the eyes in the Middle East, Asia and Africa. The elemental composition of twenty-one kohl specimens originating from various parts of Saudi Arabia, India and the Middle East was determined by energy dispersive X-ray analysis (EDAX). The data indicates the presence of significant lead levels in two thirds (14/21) of the kohl specimens ranging from 2.9-100% (mean 48.5%). Other less frequent elements present in kohl preparations include aluminu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 13 publications
1
37
0
Order By: Relevance
“…Occasionally, SGH can lead to bilateral orbital haemorrhages with loss of vision needing surgical intervention. 3 Kohl eyeliner 4 was worn by both men and women in ancient Egypt for adornment and to reduce solar glare and ward off evil spirits. How the practise originated is less clear.…”
Section: Commentmentioning
confidence: 99%
“…Occasionally, SGH can lead to bilateral orbital haemorrhages with loss of vision needing surgical intervention. 3 Kohl eyeliner 4 was worn by both men and women in ancient Egypt for adornment and to reduce solar glare and ward off evil spirits. How the practise originated is less clear.…”
Section: Commentmentioning
confidence: 99%
“…In addition, kohl is known to prevent sun glare, thus it was used by Bedouins in the Arab Peninsula. Previous studies [2][3][4] have shown that kohl contains toxic heavy metals, such as lead, and case studies have revealed that blood levels were significantly higher in individuals who used kohl compared to ones who did not. It was also shown that blood levels in infants of kohl using mothers were considerably higher than those of non-kohl using mothers (5.2 g/dl versus 2.8 g/dl) [5].…”
Section: Introductionmentioning
confidence: 97%
“…Of the techniques [2,3], such as energy dispersive X-ray analysis (EDAX) and X-ray powder diffraction (XRPD) that have been used to characterize the chemical content of kohl, many require the introduction of vacuum and energy (high excitation source), thus modifying the sample to be analyzed. In contrast, Raman spectroscopy is nondestructive and may be performed under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…There has been studies and scientific debate on the exposure of the eyes to lead as a result of the use of cosmetics [15][16][17][18][19] . Underarm cosmetics are being investigated as a possible cause of breast cancer 20 while talcum powders have been observed to contain as bursiform and sizeable concentrations of Ni, Cr and Co 20 .…”
Section: Introductionmentioning
confidence: 99%